(untitled) (London Journal of Medical and Health Research, 2024)
Body flaccidity is one of the most significant physical concerns today. Flaccidity manifests as weakened, rough skin with a noticeable loss of tone and elasticity, deviating from the aesthetic ideal. The causative factors are both intrinsic, such as the natural aging process, and extrinsic, including stress, alcohol, and sun exposure, among others. Women are the gender most prone to flaccidity and are more vulnerable to societal and media messages, leading these physiological changes to have a negative impact on their body image perception and psychological well-being. Here, we present a clinical, open-label study, involving 18 patients, who were treated for their flaccidity areas with Low 1.5 HA pbserum, a cocktail of recombinant enzymes, collagenase, lipase, and lyase, together with high molecular weight hyaluronic acid (HA). Our study showed that Low HA 1.5 pbserum significantly improved body flaccidity after 36 days of treatment. It was effective against skin flaccidity in 92 % of patients. It also improved firmness in 92 % of women and reduced fat in 84 %. We also measured the patient satisfaction and 93% of women were satisfied with the treatment. The product was well tolerated, permitting a good quality of life.